2013
DOI: 10.3168/jds.2012-5610
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein responses in dairy cows to changes in postruminal supplies of arginine, isoleucine, and valine

Abstract: An ideal profile of essential AA (EAA) can improve the efficiency of metabolizable protein (or PDIE, the equivalent in the INRA feeding system) utilization in dairy cows. Compared with other EAA, existing recommendations for the requirements of Arg, Ile, and Val are few and inconsistent. Four multiparous Holstein dairy cows at 22±6 wk of lactation received 4 treatments (duodenal infusions of 445±22.4 g/d of an EAA mixture complementing a low-protein diet in a 4×4 Latin square design with a period length of 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 25 publications
5
45
1
Order By: Relevance
“…Correlations amongst many plasma AA concentrations (Figure 7) resembles the network of interactions which have been documented among nutritionally important minerals (e.g., Jurgens molecules that should be considered in total, rather than individually, while also considering antagonisms and interactions amongst them (Haque et al, 2013). Such factors may explain the inconsistency of data obtained from studies that have supplemented ruminally protected AA and/or attempt to change the AA profile of intestinally delivered protein (Robinson, 2010).…”
Section: Inter-correlations Of Plasma Aamentioning
confidence: 49%
See 1 more Smart Citation
“…Correlations amongst many plasma AA concentrations (Figure 7) resembles the network of interactions which have been documented among nutritionally important minerals (e.g., Jurgens molecules that should be considered in total, rather than individually, while also considering antagonisms and interactions amongst them (Haque et al, 2013). Such factors may explain the inconsistency of data obtained from studies that have supplemented ruminally protected AA and/or attempt to change the AA profile of intestinally delivered protein (Robinson, 2010).…”
Section: Inter-correlations Of Plasma Aamentioning
confidence: 49%
“…Methods used to predict limiting AA, and therefore AA requirements, of lactating dairy cows are numerous, including culturing bovine mammary cells in AA mediums to determine effects on milk protein synthesis (Clark et al, 1978;Arriola Apelo et al, 2014b), evaluating changes in plasma AA concentrations and its impacts on milk and milk protein production during intravenous (Fisher, 1972) or post-ruminal supplementation of single or combinations of AA (Clark, 1975;Clark et al, 1978;Schwab et al, 1992a;1992b;Weekes et al, 2006;Haque et al, 2012;2013), doseresponse relationships between animal performance and N inputs (NRC 2001), calculating the extraction efficiency of the mammary gland by determining arteriovenous differences of AA across the mammary gland (Mulrooney et al, 2009;Christen et al, 2010), as well as uptake of AA from the small intestine (and the mammary gland) relative to their output in milk (Piepenbrink et al, 1998). However, results are variable and inconsistent, with some methods using metabolic models to predict AA supplied from experimental rations, and data is interpreted differently amongst researchers with overall levels highly dependent on base rations, which varied amongst experiments.…”
Section: Determining Plasma Aa Concentrationsmentioning
confidence: 99%
“…Arg was not likely limiting as Arg per se for synthesis of milk proteins, but rather it was needed by the mammary gland for other metabolic functions including the synthesis of Glu and Pro. Haque et al (2013) showed no protein synthesis response to duodenal infusions of Arg for cows fed a proteindeficient diet. Phe frequently ranks high as a limiting EAA for diets such as fed in this experiment because such diets are relatively low in both Phe and Tyr and the lactating bovine mammary gland can synthesize Tyr from Phe (Jorgensen and Larson 1968).…”
Section: Plasma Amino Acidsmentioning
confidence: 92%
“…However this seems unlikely since the manufacturing technology of this RP-Phe was the same as the RP-Lys product evaluated in Sakkers et al (2013) which was measured in vivo to have a rumen escape of 52% of consumed Lys. Haque et al (2013) (Kaufman 1971), the first step in catabolizing Trp to synthesize serotonin and, since Trp levels in the plasma of both Phe supplemented treatments decreased vs.…”
Section: Discussionmentioning
confidence: 99%